Comprehensive Analysis of Prognostic Microenvironment-Related Genes in Invasive Breast Cancer - Shi, Yingrong; Chen, Si; Xing, Huijuan; Jiang, Guanglie; Wu, Nan; Liu, Qiannan; Sakamoto, Norihiro; Kuno, Takayoshi; Sugiura, Reiko; Xiao, Qinghuan; Jin, Feng; Fang, Yue; et al. (Frontiers in Oncology, 2022)
Recent studies reveal that tumor microenvironment contributes to breast cancer (BRCA) development, progression, and therapeutic response. However, the contribution of the tumor microenvironment-related genes in routine diagnostic testing or therapeutic decision making for BRCA remains elusive. Immune/stromal/ESTIMATE scores calculated by the ESTIMATE algorithm quantify immune and stromal components in a tumor, and thus can reflect tumor microenvironment. To investigate the association of the tumor microenvironment-related genes with invasive BRCA prognosis, here we analyzed the immune/stromal/ESTIMATE scores in combination with The Cancer Genome Atlas (TCGA) database in invasive BRCA. We found that immune/stromal/ESTIMATE scores were significantly correlated with the invasive BRCA clinicopathological factors. Based on the immune/stromal/ESTIMATE scores, we extracted a series of differential expression genes (DEGs) related to the tumor microenvironment. Survival analysis was further performed to identify a list of high-frequency DEGs (HF-DEGs), which exhibited prognostic value in invasive BRCA. Importantly, consistent with the results of bioinformatics analysis, immunohistochemistry results showed that high SASH3 expression was associated with a good prognosis in invasive BRCA patients. Our findings suggest that the tumor microenvironment-related HF-DEGs identified in this study have prognostic values and may serve as potential biomarkers and therapeutic targets for invasive BRCA.